Group colorings and Bernoulli subflows - Gao, Su, 1968-; Jackson, Steve, 1957-; Seward, Brandon, 1987- (Memoirs of the American Mathematical Society, 2016)
In this paper the authors study the dynamics of Bernoulli flows and their subflows over general countable groups. One of the main themes of this paper is to establish the correspondence between the topological and the symbolic perspectives. From the topological perspective, the authors are particularly interested in free subflows (subflows in which every point has trivial stabilizer), minimal subflows, disjointness of subflows, and the problem of classifying subflows up to topological conjugacy. Their main tool to study free subflows will be the notion of hyper aperiodic points; a point is hyp.